Assessment of aged health problems in Ido Usi Local Government Area of Ekiti State, Nigeria (2011)
Ageing is a gradual process that begins from birth till death. It is characterized by the persistent wearing away and repair or replacement activities of the body but more remarkable at old age. The study assessed the old age health problems of old age people in Ido Usi Local Government Area of Ekiti state. Stratified and purposive sampling technique was used to select a sample of200 participants comprising of both male and female aged 60 years and above. As self developed and validated structured questionnaire was used for data collection. Reliability coefficient of 0.72 was obtained for the instrument using crombach's alpha coefficient (r). The data was analyzed using descriptive statistics of frequency counts, percentages and chi-square x2 at 0.05 alpha level. The result showed that old age people have a decrease in biological functioning of their body system as they suffered defective symptoms in their eye sight, bone and muscle, skin and hair, sex organs response, diabetes and insomnia. Suggestion was made on coping strategies for successful and active ageing.